The Effect of Thickness of Silver Thin Film on Structural and Optical Properties of Porous Silicon - Çetinel, A.; Özdoğan, M.; Tarhan, Enver; Utlu, G.; Tarhan, Enver; Artunç, N.; Şahin, G.; Tarhan, Enver (World Scientific Publishing Co. Pte Ltd, 2017)
In this study, porous silicon (PS) samples were prepared on n-type silicon (100) wafers by electrochemical etching method, varying the current density from 20 to 100mA/cm2 and keeping constant HF concentration (10%) and etching time of 15min. Then, Ag thin films, which have 10, 50 and 100nm film thicknesses, were deposited on PS layers by using thermal evaporation to investigate the influence of Ag film thickness on structural and optical properties of PS. The structural and optical properties of PS and Ag deposited PS layers have been investigated by XRD, FE-SEM, Raman and photoluminescence (PL) spectroscopy. FE-SEM XRD and Raman analyzes indicate that average pore size and porosity of PS layers increase with the increasing current density. Further, Ag nanoparticles have embedded in pore channel. PL measurement reveals that higher porosity of PS would be better to form the Ag-PS nano-composite material leading to stronger PL band. The PL spectra of PS and Ag-PS samples indicate that PL bands show blue shift with increasing current density and film thickness. Consequently, it has been found that the structural and optical properties of PS depend on current density and Ag film thickness individually.
Keywords: Crystal structure; Luminescence; Semiconductors; Raman spectroscopy; Thin films